The Role of the Digital Economy in Increasing the Competitiveness of MSMEs in Indonesia - Wati, Aprilia Candra Purnama; Agustianto, Mochammad Andre (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2025)
The digital economy is the main force driving economic transformation throughout the world, especially in Indonesia. The rapid progress of information and communication technology has caused various sectors to adopt digital platforms to increase operational efficiency and expand market access. This essay focuses on how Indonesian MSMEs, which are the backbone of the country's economy, can take advantage of the digital economy to increase their competitiveness. To be able to develop amidst increasing market competition, MSMEs must strategically integrate digital technology such as social media, fintech and e-commerce. This research uses qualitative methods, literature research and secondary data to highlight the benefits of the digital economy for MSMEs. Key benefits include improved operational efficiency and increased customer reach in both domestic and international markets. However, MSMEs face significant challenges in utilizing digital technology, including low levels of digital literacy, inadequate technological infrastructure in rural areas, and a lack of regulatory support for digital economic growth. The findings show that the digital economy encourages innovation in product development, marketing and business management, thereby providing opportunities for MSMEs to increase competitiveness. To overcome these challenges, collaboration between the government, private sector, educational institutions and the MSME community is needed to create an inclusive and sustainable digital ecosystem. The article offers strategic recommendations for optimizing the benefits of the digital economy for MSMEs, including supportive regulations, infrastructure development, and digital literacy training.